Dynamic spectrum allocation scheme for heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Islam, Shayla; Hashim, Wahidah; Pandey, Bishwajeet (Springer US, 2017)
Recently, femtocells (HeNBs) are deployed in heterogeneous network (HetNets) attributable to the addition of coverage, capacity and impeccable spectrum efficiency in private buildings/office complexes surroundings. This unplanned placement of HeNBs creates co-channel interference (CCI) in orthogonal frequency division multiple access (OFDMA). As a result service, disruption occurred at the macrocell user and femtocell user. Therefore, with always expanding interest for frequency spectrum, there is have to make available more resource allocation in order to permit more quantities of unlicensed clients to transmit their signals in the authorized groups. Cognitive-based approaches may increase the spectrum efficiency by sharing resources opportunistically from unlicensed/licensed network. However, spectrum management processes quite difficult, and a lot of chance to occur interference at the cell-edge users. Therefore, a dynamic spectrum allocation scheme is proposed for OFDMA based HetNets. The proposed scheme efficiently reduces the interferences through subchannel detection. To accomplish the CCI mitigation, the proposed scheme is functioning using the energy exposure with group creation algorithm for subchannel detection. Finally, the detected subchannel is allocated through applying power allocation algorithm. The simulation results represent that proposed scheme is able to maximize the spectrum detection and enhanced the spectral efficiency. The improved spectral efficiency recuperates the CCI situation at underlay HetNets.